2000
DOI: 10.1161/01.atv.20.12.2614
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Sphingomyelin Level as a Risk Factor for Coronary Artery Disease

Abstract: Abstract-Only a fraction of the clinical complications of atherosclerosis are explained by known risk factors. Animal studies have shown that plasma sphingomyelin (SM) levels are closely related to the development of atherosclerosis. SM carried into the arterial wall on atherogenic lipoproteins may be locally hydrolyzed by sphingomyelinase, promoting lipoprotein aggregation and macrophage foam cell formation. A novel, high-throughput, enzymatic method to measure plasma SM levels has been developed. Plasma SM l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
265
3
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(286 citation statements)
references
References 31 publications
14
265
3
4
Order By: Relevance
“…Furthermore, serum sphingomyelin decreased in recovery from exercise with a similar response in most species. Total serum sphingomyelin relates to risk of cardiovascular disease (CVD) (18,29), so the decrease in recovery could reflect a common pathway by which exercise is cardioprotective and promotes insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, serum sphingomyelin decreased in recovery from exercise with a similar response in most species. Total serum sphingomyelin relates to risk of cardiovascular disease (CVD) (18,29), so the decrease in recovery could reflect a common pathway by which exercise is cardioprotective and promotes insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Serum ceramides are increased in obesity and type 2 diabetes (13,17) and are associated with the development of ath- erosclerosis (18). Serum ceramides are thought to promote insulin resistance by activating intracellular inflammatory cascades and increasing macrophage cytokine production via Toll-like receptor 4 signaling (6).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps through these same mechanisms, ceramides may contribute to the early stages of atherosclerosis (Ichi et al ., 2006; Bismuth et al ., 2008) and the accumulation of ceramide in the myocardium may cause cardiac dysfunction in obese and diabetic individuals, even in the absence of hypertension and myocardial ischemia (Park & Goldberg, 2012). It is noteworthy that Jiang and colleagues found that plasma levels of sphingolipids are an independent risk factor for coronary heart disease (Jiang et al ., 2000). In animal models, the ceramide accumulation within the myocardium is responsible for a direct toxic effect on myocardial fibrils, cardiomyocytes apoptosis, and altered cardiac metabolism (Park & Goldberg, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has also shown a probable implication of sphingolipids in atherosclerosis. Jiang et al have shown that plasma sphingomyelin concentration is correlated with the development of atherosclerosis and furthermore was also shown to be an independent predictor of coronary artery disease [1]. The accumulation of sphingolipids noted in atherosclerosis appears to influence the atherogenic process by affecting lipoprotein metabolism and lipid efflux and by acting as a key signaling molecule.…”
Section: Introductionmentioning
confidence: 99%